Effects of a Behavioral Program on Exercise Adherence and Exercise Self-Efficacy in Community-Dwelling Older Persons. (30th December 2013) - Azizan, Azliyana; Justine, Maria; Kuan, Chua Siew
Abstract : Background. This study determines the effects of a behavioral program on exercise adherence (step counts) and level of exercise self-efficacy (ESE) in community-dwelling older persons. Methods. Sixty-three participants (age = 63.8 ± 4.5 years) were enrolled in this controlled quasi-experimental study. They were divided into 3 groups: (1) EBG performed a 6-week exercise intervention followed by a 5-week behavioral program, (2) EG performed exercise intervention similar to EBG, and (3) control group (CG) did not receive any interventions. Step counts were measured based on the scores recorded by a pedometer while ESE was measured by a self-reported ESE scale. Results. Data analysis showed significant differences due to time effect (F ( 1, 2 ) = 39.884, P < 0.01, and η = . 399 ); time and group interactions (F ( 2, 60 ) = 112.683, P < 0.01, and η = . 790 ); and between-group effect (F ( 2, 60 ) = 12.524, P < 0.01, and η = . 295 ) for step counts. As for ESE, significant differences were also found for time effect (F ( 2, 4 ) = 66.628, P < 0.05, and η = . 526 ); time and group interactions (F ( 2, 60 ) = 4.562, P = 0.014, and η = . 132 ); and between-group effect (F ( 2, 60 ) = 13.632, P < 0.05, and η = . 312 ). EBG presented with significantly higher mean changes for both step counts and ESE compared to other groups (all P < 0.05 ). Conclusion. This study suggests that the addition of a behavioral program is superior as compared to exercising alone on increasing exercise adherence and level of self-efficacy in older persons.